Effects of long-haul transmeridian travel on player preparedness: Case study of a national team at the 2014 FIFA World Cup. Issue 4 (April 2017) - Fowler, Peter M.; McCall, Alan; Jones, Mark; Duffield, Rob
Abstract: Objectives: Describe the effects of eastward long-haul transmeridian air travel on subjective jet-lag, sleep and wellness in professional football (soccer) players prior to the 2014 FIFA World Cup in Brazil. Design: Single cohort involving twenty-two male professional football players representing a national football team. Methods: Data was collected from players prior to and following international travel from Sydney, Australia to Vitoria, Brazil. In total there were three flights, 19-h and 14, 695 km of travel east across 11 time-zones. Training load and wellness measures were obtained in the week prior to and following travel, whilst sleep and jet-lag measures were collected on the day prior to travel (Pre), the day of arrival and for five days following travel (Post 1–5). Results: Compared to Pre, perceived jet-lag was significantly increased on Post 1 to 4, with significantly greater levels on Post 1 compared to Post 5 ( p  < 0.05). Self-reported sleep duration during travel was 5.9 (4.8–7.0) h, which was significantly lower than all other nights ( p  ˂ 0.01), except for the night of arrival, where time in bed and sleep duration were significantly reduced compared to Post 1–4 ( p  ˂ 0.01). Lastly, compared to the week prior to travel, mean wellness was significantly reduced during the week following travel ( p  ˂ 0.01). Conclusions: Self-reported sleep disruption during and following eastward long-haul transmeridian air travel, together with exacerbated jet-lag symptoms may result in reduced player wellness. Consequently, player preparedness for subsequent training and competition may be impeded, though physical performance data is lacking.